SOCIAL MEDIA AND NONVIOLENT PROTEST MOVEMENTS: A CONTEMPORARY REVIEW OF THE ENDSARS MOVEMENT - Olaoluwa Babatunde OYINLOYE; Adeshina Iyanuoluwa OMOTAYO (International Studies Journal)
The use of social media platforms such as Facebook, Instagram and Twitter were pivotal in the EndSARS protest against police brutality. It is a strongly held view that what is aired by the media during conflict often serves as one of the instruments of resolving or escalating conflict. The EndSARS movement employed various nonviolent strategies and tactics to advance its objectives. One of the key strategies used was peaceful mass protests and demonstrations. This article highlights a view of the EndSARS movement, focusing on the role of social media in facilitating nonviolent protest movements. The EndSARS movement emerged in Nigeria in 2020, aiming to end police brutality. This study explored how social media has been used to facilitate protests movements globally and examines the impact of social media platforms, such as Twitter and Facebook, in mobilizing activists, amplifying voices, and disseminating information. The study was anchored on the collective identity theory. The analysis highlights the challenges, successes and limitations of using social media for nonviolent protests, drawing implications and lessons for future movements. The study employed a qualitative data collection method and twelve (12) respondents comprising of police officers and activists who were participants in the EndSARS protests were interviewed.